Caribbean Report 19-07-1988 - Timmins, Jerry (anchor); King, Winston (interviewee); Tomlinson, Alan (correspondent); Clarke, Claude (interviewee); Walker, Rudolph (interviewee); Peralto, Ryan (interviewee); Goldberg, Mel (interviewee) (The British Broadcasting Corporation, 1988)
This program investigates the rumours that Guyana is considering the importation of hazardous wastes to be used as an energy source. It also looks at general elections-related violence in Jamaica and measures by the leaders of the two major political leaders to curb such violence. The death of Errol John, a dramatist of Trinidad and Tobago origin is highlighted, and the formation of a new company featuring financial services to the growing number of highly paid British sportsmen is featured.
1. Headlines: Is Guyana planning to import toxic waste? ; Will there be peace in the run-up to the Jamaican election campaign? ; Exciting business proposition for producers of cut flowers. (00:06-00:24)
2. Rumours have been circulating in Guyana that the government intends to import toxic waste into the country. Jerry Timmins interviews Winston King, Executive Chairman of Guyana’s Natural Resources Agency to find out if there is any basis to the rumours. Mr. King has been consulting with two American companies who have proposed shipping industrial waste into Guyana, the intent being that the waste would be burned to produce power. King hastens to add however, that the project will not be approved till the government of Guyana is satisfied about a number of things, including 1. That what is being brought in is not toxic waste as defined by the Environmental Protection Agency of the United States, 2.That what comes in is primarily in liquid form and 3. That the environmental impact is not injurious to the health of the population of the health of the flora and fauna. (00:29 -04:06)
3. The annual convention of the Jamaica Labour Party was marred when a busload of JLP supporters went on a rampage through a shanty town traditionally loyal to the opposition People’s National Party. The action resulted in the death of one man and the wounding of six others. This violence has occurred in the run up to general elections in Jamaica. BBC’s Caribbean correspondent Alan Tomlinson takes a critical look at the prospects for a peaceful campaign when the elections are called. He interviews the PNP’s Claude Clarke, who comments on the peace initiatives being taken to curb violence between the two main parties involved in the elections. (04:08-07:19)
4. Trinidadian actor /playwright Errol John dies in London at the age of 64. The actor was well known for his most famous play ”Moon on a Rainbow Shawl”. Jerry Timmins interviews John’s friend and fellow Trinidadian Rudolph Walker, who comments on John’s love for his homeland of Trinidad and his sense of fulfillment in his career. Walker remembers John as a shy, generous person whose full potential was not realized although he was a very talented actor and playwright. (07:27-10:27)
Keywords: Hazardous wastes -- Incineration -- Guyana.; Hazardous wastes -- Management.; Renewable energy sources -- Guyana.; Financial planning industry -- Great Britain.; Dramatists, Trinidadian and Tobagonian -- Great Britain.; John, Errol.; Moon on a Rainbow Shawl.; Jamaica Labour Party.; People's National Party (Jamaica)